Co-Designing Cultural Heritage: Case Studies of Chinese-Indonesian Identity - Chaysalina, Inne; Dharmada, Glary (Universitas Ciputra, 2025)
The preservation of Chinese-Indonesian culture is increasingly challenged by urban development, generational shifts, and fragmented top-down policies. This study investigates how a collaborative design approach—grounded in participatory planning, stakeholder co-creation, and visual communication—can foster sustainable and inclusive cultural preservation. Using a qualitative multi-case study method, four culturally significant urban centers—Singkawang, Jambi, Surabaya, and Glodok—were analyzed. Data were collected from academic literature, government reports, and media sources, then thematically triangulated to reveal patterns of stakeholder-driven preservation. The findings show that Visual Communication Design plays a vital role in shaping cultural identity, amplifying narratives, and facilitating community dialogue through visual storytelling, media engagement, and identity design. A co-design framework is proposed to integrate cultural heritage into tourism, education, and urban revitalization. This research contributes practical strategies for inclusive heritage policies and supports the role of design in advancing Sustainable Development Goals related to culture and community.